Assessment of Development Results - Algeria - United Nations Development Programme (United Nations, 2015)
The Independent Evaluation Office of the United Nations Development Programme (UNDP) conducted a country level evaluation, an Assessment of Development Results (ADR) in Algeria in 2014. Assessments of Development Results (ADRs) are independent evaluations of the contribution of UNDP to the development results in the countries where it works. As a result of the terrorist attack on UNDP premises in December 2007 and its consequences, the ADR for Algeria looked at the period from 2009 to 2013, namely the last three years of the 2007-2011 cycle and the first two years of the current 2012-2014 programme cycle. Its objectives were: (i) to identify the progress made to achieve the expected results in the programme cycles in question; (ii) to analyse how UNDP Algeria is positioned, particularly in the post-terrorist attack context, to provide added value to the efforts made by the country in terms of development; (iii) to present the conclusions and the recommendations that will feed into the new programming frameworks of UNDP and the next country programme, scheduled to start in 2015.